Challenges in Developing High-Order Thinking Skills (HOTS): A Study of EFL Students' Thesis Statement in Writing Essay - Salmiati, Salmiati; Amri, Samsul; Syafrizal, Syafrizal (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study investigates the challenges encountered by English as a Foreign Language (EFL) students in developing High-Order Thinking Skills (HOTS), with a specific focus on the formulation of thesis statements in essay writing. As proficient essay writing necessitates the application of critical thinking skills, we examine the hurdles faced by EFL students during this cognitive process. Through a comprehensive analysis, this research sheds light on the specific difficulties and explores potential avenues for enhancing HOTS development in the context of thesis statement construction. The findings contribute valuable insights to pedagogical strategies aimed at fostering advanced cognitive skills among EFL learners. Thus, this study tried to analyze students’ thesis statement . The results of analysis revealed that students’ thesis statements could be categorized into good thesis statements. Based on the 14 students’ thesis statement in their essay the students’ score got 70.71, with categories as good. And the results also show that the average level of the students’ analyzing (C4) tends to be higher compared than the evaluating (C5) and creating (C6) levels, namely 85.71 (C4), 78.57 (C5), and 55.35 (C6).